HUBUNGAN PERSEPSI TENTANG NILAI HIKMAH PADA TOPIK KIMIA DENGAN RELIGIUSITAS - Nasution, Nikita Khairani; Darmana, Ayi (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
Science plays an important role in education and is a subject that contributes to the development of science in the world, one of which is chemistry. With the characteristics as attitudes, chemistry can be integrated into the character values of Islamic education. The process of values has the aim of monitoring the selfimplantation that science comes from the Quran. This study aims to determine the relationship between perceptions of the value of wisdom with religiosity and to find out the differences between male and female religiosity. The study was conducted on students taking value education courses in 2021. This study used instruments in the form of a perception questionnaire about the value of wisdom on the topic of chemistry and a religiosity questionnaire. The results showed that there was a significant relationship between perceptions of the value of wisdom on the topic of chemistry and religion, which was marked by a significance value of 0.039 < 0.05. There is a difference between the religiosity of male students and female students with a significance value of 0.040 < 0.05 indicating Ha is accepted and H0 is rejected.